Integrating a comprehensive index and the SWAT+ model to assess drought characteristics and risks under solar radiation modification - Hongrong Du; Mou Leong Tan; Narimah Samat; Zhongli Chen; Fei Zhang (Ecological Indicators, 2025)
Assessing changes in drought under solar radiation modification (SRM) requires a comprehensive approach that accounts for the complex interactions between atmospheric, hydrological, and ecological systems in tropical environments. This study integrates a Comprehensive Drought Index (CDI) with the Soil and Water Assessment Tool Plus (SWAT+) model to evaluate the impacts of SRM on drought hazards, vulnerabilities, and risks in the Kelantan River Basin, Malaysia. The CDI integrates precipitation, streamflow, and soil moisture from SWAT+ and is compared to the Standardized Precipitation Index (SPI) and Standardized Streamflow Index (SSI). GeoMIP6 climate models under two SSPs (SSP2-4.5 and SSP5-8.5) and two SRM scenarios (G6solar and G6sulfur) were bias-corrected and integrated into SWAT+ to project future drought conditions. A copula-based joint probability analysis was used to explore the interdependencies between drought indices and understand compound drought risks. The results indicate that CDI had a stronger correlation with SPI than SSI during the historical period, but this correlation weakened under future scenarios, suggesting that the climate scenarios affect precipitation, streamflow, and soil moisture, which in turn influence the relationships between drought indices. CDI proved effective in detecting droughts that SPI and SSI missed, underscoring its potential for drought assessment in tropical regions. Severe droughts projected under the SSP5-8.5 scenario, while SSP2-4.5 showed moderate drought. G6solar showed lower drought risks compared to other three scenarios, while G6sulfur resulted in drought patterns similar to SSP5-8.5. Joint probability analysis revealed a higher likelihood of concurrent drought events in future projections. The drought risk assessment showed significant spatial variability across the KRB, with population density and poor soil retention increasing vulnerability. SSP5-8.5 and G6sulfur exhibited shorter drought return periods compared to G6solar and SSP2-4.5, indicating a higher drought risk, highlighting the need for adaptive water resource management. This study offers a robust framework for drought assessment in tropical basins.